Interest Rates and Volume Net Foreign Sell on Stock Prices with Profitability as Mediating in Indonesian Banking - Dewi, Putu Dianita Cahya; Pradnyani, Ni Luh Sri Purnama; Suarjana, I Wayan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Global interest rate increases, particularly The Fed’s 5.5% hike, and Bank Indonesia monetary tightening have put a great deal of strain on Indonesia’s banking industry, affecting stock prices through shifts in interest rates, foreign investor behavior, and profitability. This study investigates the effect of interest rates and net foreign sell volume on stock prices with profitability as a mediating variable in the Indonesian banking sector. Using a quantitative method, the research utilizes secondary data from 31 banking companies listed on the IDX during 2020 - 2024, producing 155 observations. Data were analyzed using Structural Equation Modeling with SmartPLS 4.1.1.6. The results show that interest rates and net foreign sell have a negative and significant impact on both profitability and stock prices. Profitability has a positive and significant effect on stock prices, and it partially mediates the influence of interest rates and net foreign sell on stock prices. These results support the signalling theory, where rising interest rates and increased foreign sell off act as negative signals for investors, reducing confidence and suppressing stock performance. The research highlights the importance of maintaining financial stability and investor confidence amid global financial volatility.